Neurobiological correlates of internet gaming disorder: similarities to pathological gambling - Fauth-Bühler, Mira; Mann, Karl (Addictive behaviors, 2017)
The number of massively multiplayer online games (MMOs) is on the rise worldwide along with the fascination that they inspire. Problems occur when the use of MMOs becomes excessive at the expense of other life domains. Although not yet formally included as disorder in common diagnostic systems, internet gaming disorder (IGD) is considered a “condition for further study” in section III of the DSM-5. The current review aims to provide an overview of cognitive and neurobiological data currently available on IGD, with a particular focus on impulsivity, compulsivity, and sensitivity to reward and punishment. Additionally, we also compare these findings on IGD with data from studies on pathological gambling (PG)-so far the only condition officially classified as a behavioral addiction in the DSM-5. Multiple similarities have been observed in the neurobiology of IGD and PG, as measured by alterations in brain function and behavior. Both patients with IGD and those with PG exhibited decreased loss sensitivity; enhanced reactivity to gaming and gambling cues, respectively; enhanced impulsive choice behavior; aberrant reward-based learning; and no changes in cognitive flexibility. In conclusion, the evidence base on the neurobiology of gaming and gambling disorders is beginning to illuminate the similarities between the two. However, as only a few studies have addressed the neurobiological basis of IGD, and some of these studies suffer from significant limitations, more research is required before IGD's inclusion as a second behavioral addiction in the next versions of the ICD and DSM can be justified.